2019
DOI: 10.1080/09513590.2019.1632090
|View full text |Cite
|
Sign up to set email alerts
|

Experience of using time lapse microscopy in the IVF program in patients with good ovarian reserve

Abstract: The aim of this study is to evaluate the outcomes of single embryo transfer in patients with good ovarian reserve in the IVF program using time-lapse microscopy. This is a retrospective cohort study in a private IVF center in Russia. Comparison was done between 90 IVF cycles using time-lapse (study group) and 113 IVF cycles using standard culture (control group). Within each group, subgroups were selected with selective transfer of one embryo for 5 days (5SET) and elective transfer of one embryo for 5 days (5e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other recent studies have suggested new markers and grading models for day 5 blastocyst embryos based on TLI tracking. One study reported a strong correlation between spontaneous blastocyst collapse and pregnancy outcomes 38 . In another study, it was shown that TLI streaming can be exploited to automatically classify Inner Cell Mass (ICM) and Trophectoderm grading 22 .…”
Section: Related Workmentioning
confidence: 99%
“…Other recent studies have suggested new markers and grading models for day 5 blastocyst embryos based on TLI tracking. One study reported a strong correlation between spontaneous blastocyst collapse and pregnancy outcomes 38 . In another study, it was shown that TLI streaming can be exploited to automatically classify Inner Cell Mass (ICM) and Trophectoderm grading 22 .…”
Section: Related Workmentioning
confidence: 99%